2005
DOI: 10.1016/j.febslet.2005.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A phosphorylates and regulates dimerization of 14‐3‐3ζ

Abstract: Recognition of phosphorylated serine/threonine-containing motifs by 14-3-3 depends on the dimerization of 14-3-3. However, the molecular cues that control 14-3-3 dimerization are not well understood. In order to identify proteins that control 14-3-3 dimerization, we analyzed proteins that have effects on 14-3-3 dimerization and report that protein kinase A (PKA) phosphorylates 14-3-3f at a specific residue (Ser58). Phosphorylation by PKA leads to modulation of 14-3-3f dimerization and affect its interaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 33 publications
1
60
1
1
Order By: Relevance
“…Using an in vivo-based approach, Chaudhri et al (2) found that the isoform preferentially formed heterodimers with no observable homodimer formation. In addition phosphorylation influences the dimerization process (43,44).…”
Section: Resultsmentioning
confidence: 99%
“…Using an in vivo-based approach, Chaudhri et al (2) found that the isoform preferentially formed heterodimers with no observable homodimer formation. In addition phosphorylation influences the dimerization process (43,44).…”
Section: Resultsmentioning
confidence: 99%
“…Two additional point mutants of 14-3-3 isoforms have been well characterized; mutation of serine 58, known to be phosphorylated by PKA or PKB/AKT1, to alanine (S58A) induces constitutive dimerization of 14-3-3, whereas mutation of this serine to aspartic acid (S58E) abrogates dimerization (31)(32)(33). However, as shown in Fig.…”
Section: Interaction Between Gpsm3 and 14-3-3 Family Membersmentioning
confidence: 99%
“…2G, neither of these mutations to serine 58 affected interaction with GPSM3, suggesting that the GPSM3 interaction with 14-3-3 is independent of the dimerization status of 14-3-3. Homo-and heterodimerization of 14-3-3 proteins is thought to be important for their cellular functions (33). The 14-3-3 dimer adopts a cup-like shape that can interact simultaneously with two binding sites within the same protein, thereby inducing conformational change and regulating protein activity or regulating other interactions via competition or occlusion.…”
Section: Interaction Between Gpsm3 and 14-3-3 Family Membersmentioning
confidence: 99%
“…Importantly, the U-shaped groove formed by homo-and heterodimers can interact with two motifs on a single, or different client proteins. This is thought to promote interactions between distinct 14-3-3 targets (9,19,20), or to alter the conformation and activity of a single client (18,(21)(22)(23). Therefore, the precise composition of each dimer is highly significant functionally, because it probably dictates the range of its possible clients.…”
mentioning
confidence: 99%
“…In vitro and in cultured cells, certain mutant dimerizationimpaired 14-3-3s have been shown to bind clients (25,26), often with similar affinities as their dimeric counterparts, but with some exceptions, they appear unable to support normal target activity (21,25,27,28). In addition, phosphorylation of Ser 58 on vertebrate 14-3-3 renders it unable to dimerize in transfected cultured cells (29), suggesting that monomerization may regulate some 14-3-3 functions.…”
mentioning
confidence: 99%